Improving Students Learning Outcomes Using the Flipped Classroom Model on the Topic of World War II dor Grade XI Students at SMA PGRI 1 Kairatu - Lololuan, Diana; Liemubun, Izzatul Uma A.R.; Borut, Salweli; Far-Far, Gazali; Sopacua, Jems (Riwayat: Educational Journal of History and Humanities, 2023)
This study aims to improve students learning outcomes on the topic of World War II by using the Flipped Classroom learning model for 11th-grade students at SMA PGRI 1 Kairatu. This research is a classroom action research conducted at SMA PGRI 1 Kairatu. The subjects of the study were 30 students in grade XI. Data collection techniques included observation, questionnaires, and written tests. The test results showed an increase in classical completeness, where at the initial test only 10 students (33%) met the Minimum Mastery Criteria (KKM), which improved to 20 students (67%) in cycle I, and in cycle II reached 28 students (93%) who achieved mastery according to the KKM. These findings indicate that the implementation of the Flipped Classroom learning model has a positive impact on improving students learning outcomes on the World War II topic in grade XI at SMA PGRI 1 Kairatu.